Role of artificial intelligence-powered conversational agents (chatbots) in musculoskeletal disorders: a scoping review protocol - Eva Madrid; Laura Vergara-Merino; Camila Micaela Escobar Liquitay; Joaquin Gonzalez Aroca; Humberto Farías; Jorge Olivares Arancibia; Álvaro Puelles (BMJ Open)
Introduction Musculoskeletal disorders (MSDs) represent a significant global health burden that leads to substantial disability with socioeconomic impact. With the rise of artificial intelligence (AI), particularly large language model-driven conversational agents (chatbots), there is potential to enhance the management of MSDs. However, the application of AI-powered chatbots in this population has not been comprehensively synthesised. Therefore, this scoping review aims to explore the current and potential use of AI-powered chatbots in managing MSDs. The review will map out the targeted diseases, the purposes of chatbot interventions, the clinical tools or frameworks used in training these systems and the evaluated outcomes in clinical settings.Methods and analysis This scoping review will follow the Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews guidelines, with a comprehensive search across multiple databases, including Medline (Ovid Medline), Embase (Ovid), ISI Web of Science (Clarivate) and ClinicalTrials.gov. We will include studies involving adults with MSDs, regardless of publication status, language or year. The scoping review will exclude studies using non-AI chatbots or human health coaches. Data extraction and synthesis will focus on demographic characteristics, chatbot methods, outcomes and thematic analysis.Ethics and dissemination Formal ethical approval is not required as this study involves neither human participants nor unpublished secondary data. The findings of this scoping review will be disseminated through professional networks, conference presentations and publication in a scientific journal.